1996
DOI: 10.1074/jbc.271.14.8192
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Glycinamide Ribonucleotide Synthetase from Chicken Liver

Abstract: Several analogs of glycinamide ribonucleotide and phosphoribosylamine have been prepared and evaluated as substrates for glycinamide ribonucleotide synthetase purified from chicken liver. Glycinamide ribonucleotide analogs include side chain modifications wherein the glycine side chain (R ‫؍‬ CH 2 NH 2 ) has been replaced by R ‫؍‬ CH 2 NHCH 3 and R ‫؍‬ CH 2 CH 2 NH 2 , ribose ring replacement by chiral cyclopentane and cyclopentene derivatives, and phosphate replacement by phosphonates. All of these, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Collectively, these results suggest a hierarchy in the sensitivity of different intracellular metabolic products to glycine levels: glutathione synthesis is most sensitive, followed by purine synthesis, with protein synthesis most resistant. This hierarchy is consistent with biochemical measurements of the K m values of the relevant enzymes: the glycyl-tRNA amino acid synthase has a lower K m for glycine (15 μM) than that found in glycinamide ribonucleotide synthetase (45 μM) or glutathione synthetase (452 μM) (26)(27)(28).…”
Section: Biochemistrysupporting
confidence: 85%
“…Collectively, these results suggest a hierarchy in the sensitivity of different intracellular metabolic products to glycine levels: glutathione synthesis is most sensitive, followed by purine synthesis, with protein synthesis most resistant. This hierarchy is consistent with biochemical measurements of the K m values of the relevant enzymes: the glycyl-tRNA amino acid synthase has a lower K m for glycine (15 μM) than that found in glycinamide ribonucleotide synthetase (45 μM) or glutathione synthetase (452 μM) (26)(27)(28).…”
Section: Biochemistrysupporting
confidence: 85%
“…A recent study reported that NT5C overexpression decreased dNTP pools and negatively regulated nucleotide synthesis [ 50 ]. PPAT is a key enzyme in the first reaction of de novo purine biosynthesis [ 51 ] and XDH is involved in the oxidative metabolism of purines [ 52 ]. At the end of incubation, the beak of chicken embryo is unchanged and hatching muscle development matures.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for compartmentalization has largely relied on kinetic arguments. Specifically, the product of the first reaction in the de novo purine biosynthetic pathway, PRA, has a very short solution half-life and may directly transfer to the subsequent enzyme, GART, through complexation of the two enzymes [4, 31, 32]. Similarly, GART catalyzes non-concerted steps within the same pathway (Figure 1) and requires the activity of FGAMS for the fourth step raising the possibility that FGAMS interacts with GART [33].…”
Section: Discovery Of a Metabolon In Purine Metabolism – The Purinosomementioning
confidence: 99%